The Carpetbaggers of Kabul and Other American-Afghan Entanglements : Intimate Development, Geopolitics, and the Currency of Gender and Grief - Fluri, Jennifer L.; Lehr, Rachel, 1945- (Book collections on Project MUSE., 2017)
The 2001 invasion of Afghanistan by United States and coalition forces was followed by a flood of aid and development dollars and "experts" representing well over two thousand organizations--each with separate policy initiatives, geopolitical agendas, and socioeconomic interests. This book examines the everyday actions of people associated with this international effort, with a special emphasis on small players: individuals and groups who charted alternative paths outside the existing networks of aid and development. This focus highlights the complexities, complications, and contradictions at the intersection of the everyday and the geopolitical, showing how dominant geopolitical narratives influence daily life in places like Afghanistan--and what happens when the goals of aid workers or the needs of aid recipients do not fit the narrative.